Effect of polyphenolic compounds from Solanum torvum on plasma lipid peroxidation, superoxide anion and cytochrome P450 2E1 in human liver microsomes - Kusirisin W. (2014)
Previous studies presented evidence that plants contain antioxidants that have free radical-scavenging properties. Overproduction of free radicals leads to oxidative stress, a factor associated with a variety of diseases, such as diabetes. Cytochrome P450 2E1 enzymes (CYP2E1) are involved in drug metabolism in the liver and metabolism of DNA-reaction generating intra-mitochondrial ROS, which leads to micro- and macro-vascular pathology in diabetes. Plant-based chemicals can affect CYP2E1 enzymes and related defense mechanisms, possibly leading to protection against oxidative stress. We investigated the effect of Solanum torvum (ST) extracts on the inhibition of CYP2E1 activity in human liver microsomes. ST extract was analyzed for antioxidant activity by the ABTS method. Polyphenolic compounds were measured by the total phenol content using the Folin-Ciocalteau reagent. Flavonoid and tannin content were analyzed by standard methods. Oxidative stress was evaluated by measuring lipid peroxidation by TBARS and superoxide anion scavenging levels in plasma from diabetic patients. Results showed that 10 mg/ml of ST had CYP2E1 catalytic inhibiting activity (57.16 %). The IC50 value of CYP2E1 catalytic inhibiting activity level was 5.14 mg/ml by concentration in a dependent manner. One gram of concentrated ST extract had an antioxidant activity index of 3.68 mg of trolox and 360.53 mg of ascorbic acid equivalent. Effects on free radical-scavenging, as measured by TBARS and superoxide anion, showed IC50 values of 20.60 and 10.26 μg/ml, respectively. Polyphenolic compounds found included phenol, flavonoid and tannin, measuring 160.30, 104.36 and 65.91 mg/g, respectively. These results imply that ST is a natural source of polyphenolic antioxidants, which have cytochrome P450 2E1 enzyme inhibiting and free radical scavenging properties, as related to lipid peroxidation and superoxide anion activity. ST could potentially be used for reducing oxidative stress in diabetes. Study for usage as a conventional medicine, including dosage and chronic toxicity in humans, should be pursued. © 2009 Bentham Science Publishers Ltd.